Types of Open-Air Museum (Skansen) in Ukrainian Carpathians - Chervinskyi , Andrii (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The problems of preservation of wooden architecture of Ukraine are discussed. The museums under opened air are organized for better preservation of the wooden architecture. The Ukrainian Museums under opened air are described and their use for tourism purposes is analyzed.